IMF Staff papers : Volume 4 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1955)
This paper outlines the payment agreements and trade agreements. Resident inconvertibility in relation to other inconvertible countries is largely organized on the basis of bilateral trade agreements establishing quotas for imports, exports, and invisibles, and of the Organization for European Economic Cooperation (OEEC) Code of Liberalization. Resident inconvertibility vis-a-vis convertible countries is implemented mainly by unilaterally imposed quantitative import and exchange restrictions that usually are subject to a high degree of administrative discretion. Under bilateral payments agreements, the partner countries undertake to affect their reciprocal current settlements in a way that will minimize the use of convertible exchange and gold. In a typical case, the two central banks open accounts in their respective currencies in each other's names, but agreements may also provide for one (main) agreement account. Settlements in convertible currencies or gold have to be made only when one partner's net debtor position in the designated accounts exceeds an amount established in the agreement as the limit up to which each partner is prepared to sell its currency for the other's currency without demanding cover.